Hannah and Hanna in Dreamland - Retallack, John (Oberon modern plays., 2018)
A story of friendship, migration and karaoke' Summer 1999. Margate's beaches are packed with day-trippers'. and its hotels filled with Kosovan asylum seekers ' including Hanna (Celia Meiras), a survivor of Europe's most recent genocide. Hannah (Lisa Payne) is from Margate and bored with life in the rundown seaside town - hanging out with her boyfriend Bull and his prejudiced mates. The only things the two sixteen-year-olds have in common are their names and their love of singing along to their favourite pop songs' Sixteen years later, Hanna returns to Margate - this time in search of a Syrian girl she befriended in Kosovo and who may have succeeded in getting across the Channel. The Calais 'Jungle' is close and attempts by its residents to reach England fill the local media. Hanna hopes her young friend will be welcome in Margate, but although the town has changed, alongside the coffee bars and vintage shops, there is still an undercurrent of hostility towards the migrants and refugees who are so desperate to enter the UK. Just as in 1999, when Hanna's arrival turned Hannah's life upside down, so her return takes the friends on a journey which Hannah from Margate would not have thought possible. Hannah and Hanna in Dreamland builds on John Retallack's award-winning earlier play, Hannah and Hanna, which has been performed extensively both nationally and internationally.